(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Field experiment was conducted to evaluate the effect of seed treatment and foliar spray with four different plants extracts viz. Lawsonia alba, Adhatoda vesica, Swertia chirayaita, Calendula officinalis, two chemicals viz. Provax-200 WP (0.4%), Bavistin (0.3%) and BAU-Biofungicide (a Trichoderma based preparation) on disease severity, yield and yield contributing characters of wheat cv. Kanchan during the period from March, 2014 to April, 2015. The highest seedling number/m2 (168.0) recorded in case of seed treatment + foliar spray with Bavistin and the lowest (133.0) in case of Lawsonia alba leaf extract at 30 DAS. The highest plant height (112.69 cm) and panical length (11.86 cm) were recorded in case of seed treatment + foliar spray with BAU-Biofungicide and the lowest in untreated control. The maximum disease severity was recorded in untreated control at all counts, but minimum disease severity was recorded in case of using seed treatment + foliar spray with BAU-Biofungicide at 4th count. The highest 1000-grain weight (41.590 g) was found in case of seed treatment + foliar spray with BAU-Biofungicide followed by seed treatment + foliar spray with Bavistin (41.340 g) and the lowest (39.073 g) in untreated control. The highest grain yield/ha (4769.85 kg) was found in case of seed treatment + foliar spray with BAU-Biofungicide and the lowest (3069.85 kg) in untreated control. Seed treatment + foliar spray with BAU-Biofungicide resulted 35.64% increase of yield over untreated control. The maximum number of grade-0 seeds (89.90 %) was recorded in case of seed treatment + foliar spray with BAU-Biofungicide and the lowest (80.1%) in case of untreated control. Therefore, BAU-Biofungicide can successfully be used for eco-friendly management of leaf blight disease of wheat for obtaining higher yield by avoiding chemicals. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 206-212